Reduction of the spread of SARS-CoV-2 coronavirus and COVID-19 disease through ventilation and air conditioning systems - Cepiński, Wojciech; Szałański, Paweł; Misiński, Jacek (Instal, 2020)
The article analyses potential ways of spreading the SARS-CoV-2 virus in typical existing ventilation and air conditioning systems in non-health facilities. The recommendations presented by ASHRAE, REHVA, EUROVENT MIDDLE EAST and Polish National Institute of Public Health (NIZP-PZH) have been used. Ventilated rooms and particular elements of the ventilation system: route and tightness of ventilation ducts, air handling units, as well as the location of the fresh air intake and exhaust air outlet were taken into account. The analysis of pressure distribution profiles in duct systems and for various air handling units types was made. A number of methods of reducing the risk of spreading COVID-19 in ventilation systems were proposed, with particular emphasis on reduction of possible air leaks. A procedure was formulated to enable the achievement of this objective.
Keywords: coronavirus; SARS-CoV-2; COVID-19; ventilation; HVAC